Struktur Pendapatan dan Kesejahteraan Rumah Tangga Petani Jeruk Manis di Kecamatan Raya Kabupaten Simalungun - Jhon Witner Purba; Novia Dewi; Yulia Andriani (Pusat Studi Industri dan Perkotaan (PSIP) Universitas Riau, 2023)
The purpose of this study was to determine the income structure and welfare of sweet orange farmer households. This research was conducted in Raya District, Simalungun Regency. The method used in this study was a survey method with a total of 57 farmers taken as respondents using a purposive sampling method, namely farmers who have productive citrus plants. Based on the results of household income analysis, it shows that the average household income of sweet orange farmers is Rp 42,897,107/cultivated area/year. The structure of household income for sweet orange farmers comes from the sweet orange farming sector (68.46%), non-sweet orange farming (19.33%) and non-agriculture (12.21%). The welfare level of sweet orange farmer households based on 7 BPS indicators is in the prosperous category (91.23%).